2020
DOI: 10.1002/rcm.8655
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of soybean green stem and foliar retention (GSFR) disease using mass spectrometry and molecular networking

Abstract: Rationale The nematode Aphelenchoides besseyi is the causal agent of green stem and foliar retention, a soybean disease recently described in Brazil. This condition can reduce soybean yield by up to 100%. However, little is known about chemical interactions between the plant and pathogen. Therefore, this work aimed to investigate metabolites from healthy soybean roots and from soybean roots that were inoculated with A. besseyi. Methods A. besseyi were multiplied in vitro with Fusarium sp. colonies in Petri dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Moreover, the interaction between soy and microorganisms, nematodes, aphids, and other insects causes distinct metabolic responses, and metabolomics is a unique approach for understanding such changes, providing insights to improve soy's response against biotic factors [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Recent works used GNPS to identify metabolite variation in soy infected by the fungus Phakopsora pachyrhizi and the nematode Aphelenchoides besseyi [78][79][80]. Both pathogens resulted in a higher production of bioactive compounds such as flavonoids, isoflavonoids, and terpenoids.…”
Section: Metabolomics and Soy An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the interaction between soy and microorganisms, nematodes, aphids, and other insects causes distinct metabolic responses, and metabolomics is a unique approach for understanding such changes, providing insights to improve soy's response against biotic factors [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Recent works used GNPS to identify metabolite variation in soy infected by the fungus Phakopsora pachyrhizi and the nematode Aphelenchoides besseyi [78][79][80]. Both pathogens resulted in a higher production of bioactive compounds such as flavonoids, isoflavonoids, and terpenoids.…”
Section: Metabolomics and Soy An Overviewmentioning
confidence: 99%
“…In addition to the four main causes of change in soy metabolism mentioned above, both qualitative and quantitative metabolic variations among soy organs are expected. To present an overview of the metabolite profile of underused soy parts, we selected metabolomics and related works which used various approaches to analyze them [38,67,[78][79][80]93,94,[98][99][100][101][102][103][104][105][106][107][108]. Using Jchem (JChem for Excel 21.1.0.787, ChemAxon (https://www.chemaxon.com accessed on 8 April 2021)) [109] and ClassyFire [110], we organized and classified the metabolites identified in soy roots, leaves, branches, and pods, as presented in Supplementary Materials Table S1-S4, respectively.…”
Section: Bioactive Compounds In Underused Soy Partsmentioning
confidence: 99%
“…The nucleoside thymidine, a DNA constituent, has been shown to have exudate function as a growth substrate for rhizosphere microorganisms in Avena barbata (Zhalnina et al, 2018) and as a metabolite involved in response to P deficiency in Glycine max (Tawaraya et al, 2014). Enriched coumarins included four chromenone glycoside derivatives (Figure 5, Data S1), previously identified in root extracts from Glycine max (Zanzarin et al, 2020). The coumarin pathway was reported as up-regulated in response to Fe limitation in white lupin (Venuti et al, 2019) and some coumarins from Arabidopsis root exudates were shown to complex Fe (Schmid et al, 2014) but coumarins have not previously been associated to arsenic response, and their role in root exudates remain unclear.…”
Section: Exudation Profile Of Arsenic Tolerance In White Lupinmentioning
confidence: 91%
“…Cooling of plant samples is usually performed by freezing in liquid nitrogen and freezer storage at −80 °C . Several studies of untargeted metabolomics of crops, including soybean, have verified the same cultivation strategies, including collection, harvesting, and storage of samples, always looking for the integrity of the samples. ,,, …”
Section: Metabolomics Workflow For the Study Of Biotic Stress In Soybeanmentioning
confidence: 99%
“…LC–MS is an analytical system that offers robustness, sensitivity, and selectivity. The technique allows for the analysis of polar and nonpolar chemical compounds without derivatization steps, covering the primary and secondary metabolites involved in plant biotic stress, and it is frequently investigated in metabolomics studies. ,,,, …”
Section: Metabolomics Workflow For the Study Of Biotic Stress In Soybeanmentioning
confidence: 99%